In situ PCR for detection and differentiation of Newcastle disease virus strains in Leghorn chickens - Hussein, Elawad A.; Bejo, Mohd Hair; Omar, Abdul Rahman; Arshad, Siti Suri; Ideris, Aini (Online Journal of Veterinary Research, 2017)
In experiment 1, six specific pathogen free (SPF) chickens were intra-nasally infected with velogenic (v) NDV strain with titre of 10⁵ EID50/0.1 mL and 6 non-infected birds were used as controls. Chickens were sacrificed at different times and tissue samples were collected for In situ PCR and immunoperoxidase staining (IPS). In situ PCR was more sensitive (P < 0.05) than IPS for detection of NDV. In a 2nd experiment, In situ PCR was done to differentiate NDV strains. Groups of 5 SPF chickens each, were infected with velogenic (10⁵EID50/0.1 mL) or lentogenic (l) NDV (103.0 EID50/0.1 mL) strains. Non-infected birds were used as controls. After sampling of tissues, an In situ PCR was developed using specific velogenic and lentogenic strain probes. In situ PCR velogenic probe was positive only to tissues infected by velogenic strain whereas lentogenic probe only with lentogenic infected-tissues. The findings suggested that the In situ PCR differentiated lentogenic from velogenic NDV virus strains.